Historiography in the Reign of Suleyman the Magnificent - Özcan, Abdülkadir (The Historical Research Foundation, 1998)
Considered to have begun with Germiyan (1) Ahmedi, Ottoman historiography.Continued during the reign of Murad II with anonymously composed works entitled Tevarih-i al-i Osman (Chronicles of the Exalted Osmanlis) that were qweated principally from historical chronologies.